the first one follows
the second
I need to find the formula for the general term in the given sequences:
---------And---------
I'm not sure how to approach this, I've looked for common differences, would it work if I used this: ?
Thank you, I appreciate your help!
Thank you for the first one!
As for the second, the first term corresponds to n=1, the second to n=2, etc. When n=1 your formula: n/(n-1)^2 actually divides by zero, and when n=2 it gives you 1.
So it just needed to be adjusted to (n+2)/(n+1)^2.
Thank you so much, you got me thinking on the right track.
My bad, I misdirected you. I meant to thank you for the formula pertaining to the second sequence: However, as for the first sequence, I had to modify to in order for it to work when n=1 and n=2. When n=1 your formula actually divides by zero, and when n=2 it produced 1.
Sorry for the inconvenience!